Effects of Different Prolonged Light Durations on Survival, Growth and Physiology of the Eelgrass Zostera marina - Zhang, Yan-Hao; Li, Jian-Du; Wu, Zhong-Xun; Yuan, Shun-Jie; Li, Wen-Tao; Zhang, Pei-Dong (Frontiers in Environmental Science, 2022)
Light is one of key environmental factors that affected the survival and growth of plants. We subjected plants of eelgrass Zostera marina to different prolonged light durations [0 (control), 2, 4, 6, 8 h d-1] for 6 weeks under controlled laboratory conditions. We measured plant response in terms of survivorship, growth, productivity, leaf pigment and carbohydrate concentrations. Survival analysis combined with growth assessment suggested that the optimum range of prolonged light durations for the establishment of Z. marina plants is 3.9 to 4.6 h d-1. The propagation coefficient of Z. marina plants exposed to 4 h d-1 was 1.4 times higher than that of plants under the control. Pearson and Mantel correlation analysis indicated that the promotion of prolonged light duration to the survival and growth of Z. marina plants mainly depended on the increase of chlorophyll content and the accumulation and synthesis of non-structural carbohydrate. The total chlorophyll content of leaves and soluble sugar content of aboveground tissues of Z. marina plants exposed to 4 h d-1 were 1.6 times and 2.9 times higher than those of plants under the control, respectively. The results will provide data that could prove helpful in the development of efficient artificial propagation technology of Z. marina plants.